Performance Analysis of Local Pekanbaru Bentonite for Reactive Solid Application of Mud Drilling - Novrianti, Novrianti; Khalid, Idham; Melysa, Richa (Journal of Earth Energy Engineering, 2018)
In oil and gas drilling activities, drilling mud is one of the most important commodities. The main mineral used as a reactive solid that works to suck fresh water and form drilling mud is bentonite. Bentonite which is used as a drilling mud in the market is mostly imported from the United States. In Indonesia there are several areas that have enough potential for bentonite minerals, namely Java, Sumatra, parts of Kalimantan and Sulawesi with reserves estimated to be more than 380 million tons. (Riyanto A, 1994). This study uses bentonite in Kulim area, Tenayan Raya City, Pekanbaru, in hopes of providing useful information input, especially in the use of bentonite minerals in drilling mud. Using local bentonite the price is cheaper and more efficient. The object observed was the effect and number of bentonite mixed with fresh water so that the rheological properties of drilling mud such as viscosity, gel strength, mud cake and filtration loss were obtained and would be in accordance with API specification 13A standards. Whereas to find out the composition and structure of local mineral clay, SEM and EDX analyzes were performed to determine the characteristics and composition of these minerals. From these tests add additives NaCO3 and NaOH as ion exchangers and add the element Na to the sludge. From SEM and EDX analysis, two samples taken in central Sumatra Sumatra can be categorized as clay Illite fe-rich and Clay Illite Platty. Rheological testing of drilling mud and chemical composition analysis of clay Illite fe-rich minerals and Clay Illite Platty in Riau, Central Sumatra and with the addition of additives NaCO3 and NaOH to local Clay, Rheology in mud based on Clay Illite Platty is obtained with Bentonite. commonly used as a basic material for the manufacture of oil and gas drilling mud with API Spec13 A.